2014
DOI: 10.1016/j.etp.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

PCB 126 perturbs hypoxia-induced HIF-1α activity and glucose consumption in human HepG2 cells

Abstract: Aerobic organisms strongly depend on the availability of oxygen for respiration and countless other metabolic processes to maintain cellular homeostasis. Under certain conditions, the amount of available oxygen can be limited. To support survival in environments with limited oxygen supply, hypoxia-inducible factors (HIFs) reprogram vital components of cellular metabolism. HIF-1α is an important mediator of acute and adaptive responses to hypoxic stress. Interestingly, the heterodimeric partner required by HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, activated AhR also associates with HIF-1β ( 33 , 34 ). In certain experimental models, this competition between AhR and HIF-α for HIF-1β results in reduced HIF-1α transcriptional activity in the case of AhR activation, or to decreased AhR transcriptional activity in the case of HIF-1α activation ( 38 40 ). However, the interaction between AhR and HIF-1 has not been evaluated during the reperfusion phase of I-R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, activated AhR also associates with HIF-1β ( 33 , 34 ). In certain experimental models, this competition between AhR and HIF-α for HIF-1β results in reduced HIF-1α transcriptional activity in the case of AhR activation, or to decreased AhR transcriptional activity in the case of HIF-1α activation ( 38 40 ). However, the interaction between AhR and HIF-1 has not been evaluated during the reperfusion phase of I-R injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, activated AhR also forms a heterodimer with HIF-1β (33, 34). In certain experimental models of AhR activation, the competition between AhR and HIF-1α for HIF-1β results in reduced HIF-1α transcriptional activity, and vice versa ( 38 40 ). However, this interaction between AhR and HIF-1α has not been evaluated in models of I-R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation by PAHs and PHAHs, the AhR is translocated to the nucleus where it forms a transcriptionally heterodimer with ARNT to regulate transcription of numerous genes, including CYP1A1 . In vitro studies with mammalian and fish cell lines have shown that there is cross‐talk between the HIF‐1α/ARNT and AhR/ARNT pathways during co‐exposure to hypoxia and AhR agonists resulting in attenuation of AhR agonist‐induced CYP1A1 expression and enzymatic activity . However, an analysis of AhR‐mediated signaling induced by dioxin in mammalian hepatoma cell lines during hypoxia exposure revealed a lack of competition for ARNT, even though CYP1A1 mRNA was down‐regulated .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we verified estrogen-like activity for both PCB126 and PCB153, in support of previous reports. 10,23,64,65 We also discovered that PCB126 exerted a stronger estrogenic activity than that of PCB153 in HepG2 cells. Importantly, we demonstrated that PCB153 and PCB126 significantly inhibited hepatic hepcidin expression through ERdependent signaling, independent of oxidative stress, BMP-6, and IL-6.…”
Section: ■ Discussionmentioning
confidence: 92%